Fair trade and sustainable development practices - Andersson, Vibeke (Diálogos Latinoamericanos, 2019)
There is consumer interest in organic and fair trade products globally. This has created a growing interest for producing agricultural products, which meet the standards for organic and fair trade products. This paper critically discusses fair trade as notion and in practice and connects the analysis of production of fair trade quinoa in a community in Southern Bolivia with Sustainable Development Goals (SDG). According to World Fair Trade Organization fair trade will improve environmental sustainability both at local level and globally as peasants in global South have opportunities to export organic products to markets in the global North, which will also have the result of empowering producers. This paper poses the question whether fair trade is alleviating poverty and supporting local producers creating environmentally sound technologies (Sustainable Development Goal 12, Target 12a) – in this case in communities in the highlands (Altiplano) in Southern Bolivia. The paper critically discusses sustainable development and the Sustainable Development Goals and questions whose interests Sustainable Development Goal 12 is primarily serving: consumers or producers. The discussion concludes that initiatives like fair trade and policies based on global goals can have unintended consequences, which are disadvantageous to local communities.